THE DRAMATIC WRITING OF ORIANA FALLACI BETWEEN JOURNALISM AND LITERATURE (Journal of Contemporary Philology, 2023)
This paper focuses on the famous “Fallaci interviews”, which are an example of what has been defined as “journalit” (Krim 1970), i.e., a non-fictional practice that is based on real events but still uses the resources of fiction and is permeated by real inventions and creative licenses (Castellana 2021; Mongelli 2015). Fallaci is a skilled playwright who knows how to “write the journalistic piece by the means of fiction and the story by the means of journalism” (Aricò 2010) to increase the dramatic character of her writings. But she also loves to show herself as a self-made woman always ready to go “on stage” (Scheer 1981: 92): the writer is a sort of “fictional witness”, a testimonial character that plays a privileged role through her writing and her presence, approaching the genre of autofiction (Doubrovsky 1977; Grell 2014; Marchese 2014, 2019) and, in some ways, of the testimonio novelizado (Beverley 1992, 1993; Jara and Vidal 1986). For these reasons, Fallaci can be put on an ideal guideline that goes from Malaparte to Pasolini (and, today, maybe to Roberto Saviano) (Altamura 2019). Like the “corsaro”, she is convinced that writing is a creative, critical, “instinctive” practice capable of undermining power, which is by its nature ambiguous and obscurantist. But, in our view, she has neither the expressiveness of Malaparte, nor the civil tension and poetic consistency of Pasolini. Her dimension seems to refer rather to the category of “midcult” (Macdonald 2018), i.e. a cultural typology based on the late or postmodern re-use of ideas, resources, languages from high culture, but not always endowed with intrinsic originality and innovativeness and able to express universal values. Net of all this, Fallaci’s writing remains an admirable example of how it is possible (even at the cost of some contradictions) to combine the ethical values ​​of journalistic-literary testimony with the codes of mass spectacularity, guaranteeing a productivity which, however, does not limit the quality standard of the work.
Keywords: New Journalism; neutrality; non-fiction; interview; testimony